Potential hazards of multidrug resistance Escherichia coli collected from wastewater on dairy farms in East Java, Indonesia - AGUS WIDODO; MIRNI LAMID; MUSTOFA HELMI EFFENDI; WIWIEK TYASNINGSIH; WURLINA WURLINA; MOHAMMAD ANAM AL-ARIF; DADIK RAHARJO; SOEHARSONO SOEHARSONO; ASWIN RAFIF KHAIRULLAH; KATTY HENDRIANA PRISCILIA RIWU; LITA RAKHMA YUSTINASARI; SHENDY CANADYA KURNIAWAN; OTTO SAHAT MARTUA SILAEN; MOSES IKECHUKWU BENJAMIN; DANIAH ASHRI AFNANI (Society for Indonesian Biodiversity, 2023)
Abstract. Widodo A, Lamid M, Effendi MH, Tyasningsih W, Wurlina, Al-Arif MA, Raharjo D, Soeharsono, Khairullah AF, Riwu KHP, Yustinasari LR, Kurniawan SC, Silaen OSM, Benjamin MI, Afnani DA. 2023. Potential hazards of multidrug resistance Escherichia coli collected from wastewater on dairy farms in East Java, Indonesia. Biodiversitas 24: 1900-1907. Escherichia coli bacteria initially reside in the digestive tract of humans and animals. This bacterium is treated with antibiotics, but this treatment may trigger antibiotic resistance. Antibiotic resistance genes found in E. coli can transfer to other bacteria, especially in the case of the emergence of multidrug resistance (MDR) bacteria. E. coli is a significant environmental contaminant on dairy farms and is frequently linked to genes that encode extended-spectrum beta-lactamase. This research focused on investigating the potential hazards of multidrug resistance E. coli collected from wastewater on dairy farms in East Java, Indonesia. The number of research samples used was 139 wastewater samples collected from 125 dairy farms in East Java, Indonesia. First, wastewater samples from dairy farms were isolated into BGLB media, then continued with culture on EMBA media, and identifying E. coli bacteria with TSIA and IMViC biochemical tests. The resistance patterns of E. coli were obtained through disk diffusion antibiotic tests on tetracycline, streptomycin, trimethoprim, chloramphenicol, and aztreonam. The results of the isolation and identification obtained 122 (87.77%) E. coli isolates. Antimicrobial susceptibility test to E. coli isolates showed 14 (11.47%) MDR E. coli isolates. The antimicrobial drug resistance pattern TE-ST-W (tetracycline, streptomycin, trimethoprim) accounted for most MDR E. coli isolates in this study, comprising 10 (36.26%); followed by TE-ST-C (tetracycline, streptomycin, chloramphenicol) with two (6.54%) MDR E. coli and two (6.54%) MDR E.coli isolates were resistant to four antibiotics, with the pattern of resistance to TE-ST-W-C (tetracycline, streptomycin, trimethoprim, chloramphenicol) antibiotic. The discovery of multidrug-resistant E. coli isolated from wastewater on dairy farms in East Java, Indonesia, is a new potential hazard that affects public health and needs solutions. One Health integration is anticipated to be used as a solution.